Traumatic Atlanto Axial Dislocation in Odontoid Aplasic Patient a Case Report - Yemişçigil, Ali; Zileli, Mehmet; Hancı, İsmail Hamit (The Bulletin of Legal Medicine, 1996)
The case that has been applied to the emergency service with complaint of severe neck pain resulting from a minor trauma, was hospitalized and examined by the Department of Neurosurgery and then was operated with the diagnosis of atlanto-axial dislocation and odontoid aplasia. Forensic report was prepared by the Department of Forensic Medicine. Odontoid aplasia is usually asymptomatic and since it made the stability of atlas insufficient, a minor neck trauma caused dislocation. The abnormality caused unexpected injuries. Since the case is rare and the injury is unexpected, it is presented. Key words: Atlanto-axial Dislocation, Atlanto-axial Instability, Odontoid Aplasia.